2022
DOI: 10.3390/metabo13010014
|View full text |Cite
|
Sign up to set email alerts
|

HIIT Ameliorates Inflammation and Lipid Metabolism by Regulating Macrophage Polarization and Mitochondrial Dynamics in the Liver of Type 2 Diabetes Mellitus Mice

Abstract: High-intensity interval training (HIIT), a new type of exercise, can effectively prevent the progression of metabolic diseases. The aim of this study was to investigate the effects of HIIT on liver inflammation and metabolic disorders in type 2 diabetes mellitus (T2DM) mice induced by a high-fat diet (HFD) combined with streptozotocin (STZ) and to explore the possible mechanisms of macrophage polarization and mitochondrial dynamics. Our results showed that HIIT can increase fatty acid oxidation-related gene (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
6
0
1
Order By: Relevance
“…Accordingly, we observed that MIT increased the LV gene expression of anti-inflammatory macrophage markers CD163 and CD206. In the livers of HFD-induced T2DM mice, upregulation of CD163 and CD206 has also been demonstrated following 8 weeks of HIIT [64]. Together, these findings suggest that endurance exercise training can act predominantly as an anti-inflammatory approach in T2DM.…”
Section: Mechanisms Of Exercise-training-induced Cardioprotectionmentioning
confidence: 73%
“…Accordingly, we observed that MIT increased the LV gene expression of anti-inflammatory macrophage markers CD163 and CD206. In the livers of HFD-induced T2DM mice, upregulation of CD163 and CD206 has also been demonstrated following 8 weeks of HIIT [64]. Together, these findings suggest that endurance exercise training can act predominantly as an anti-inflammatory approach in T2DM.…”
Section: Mechanisms Of Exercise-training-induced Cardioprotectionmentioning
confidence: 73%
“…喂养 12 周小鼠进行 8 周的有氧运动减弱了 HFD 引起的体 重增加和葡萄糖耐受不良, 并改善了胰岛素抵抗 [66] 。 此外, 运动通过抑制骨骼肌内 NF-κB 通路的激活来缓解 HFD 诱 导的炎症。Gopalan 等研究发现,12 周的有氧运动训练也能 有效改善 HFD 背景下大鼠代谢健康、胰岛素抵抗和炎症 [67] 。 研究发现, 对糖尿病大鼠进行 8 周抗阻运动能有效调控糖 尿病大鼠血糖, 改善糖尿病大鼠胰岛素抵抗 [68] 。用 8 周不 同运动干预对 HFD 诱导 IR 大鼠模型进行对比时发现,两 者均可显著降低 IR 大鼠肝脏 FFA 含量,其机制可能与运 动显著上调 IR 大鼠肝脏 AMPK、CPT1 酶含量,增强脂肪氧 化反应, 然而有氧与抗阻两者结合运动相较于单一运动干 预增加脂肪氧化的效果更为显著 [69] 。在对肥胖成人进行 6 周的低氧运动训练后发现胰岛素敏感性提高 [70] 。在对 HFD [72] 。研究表明,中等强度 的离心运动和饮食限制明显降低了 M1 极化以及促炎细胞 因子 MCP-1 和 TNF-α的分泌,同时促进了局部脂肪组织 中巨噬细胞的 M2 极化,并改善了 IR [73] 。有研究发现,对 HFD 背景下小鼠进行 12 周运动训练可有效抑制 M1 巨噬细 胞的浸润来减轻脂肪组织炎症,可能是通过降低 MCP-1 的表达来降低巨噬细胞的浸润 [74] 。同时,研究发现,高强 度间歇训练(HIIT)训练 8 周可改善 2 型糖尿病小鼠肝脏 炎症和脂质代谢紊乱,巨噬细胞 M1/M2 极化平衡 [75] 。 M1 巨噬细胞也可向 M2 巨噬细胞极化,从而改善炎症 反应。在对 HFD 诱导小鼠进行有氧间歇训练时发现,可部 分通过减少脂肪细胞大小、 增加毛细血管密度和将巨噬细 胞从 M1 转换为 M2 来逆转 HFD 诱导的皮下脂肪组织功能障 碍,最终降低胰岛素抵抗 [76] 。有学者对 HFD 诱导 T2DM 小 鼠进行急性运动,观察到可以改善白色脂肪组织(WAT) 部分的胰岛素信号,以及肥胖大鼠的 M1 巨噬细胞向 M2 巨噬细胞的表型转换, 从而增强抗炎因子 IL-10 的表达 [77] 。…”
Section: 运动调节巨噬细胞表型变化改善 Irunclassified
“…The administration of OI in the mouse models of streptozotocin (STZ)-induced type 1 diabetes (T1D) and spontaneous autoimmune diabetes reduce M1 polarization, alleviating β cell dysfunction and further improving glucose metabolism [ 78 ]. Additionally, high-intensity interval training (HIIT) in mice with type 2 diabetes mellitus (T2DM) has been shown to reduce M1 macrophage polarization in the liver, thereby decreasing liver inflammation and improving systemic inflammation associated with T2DM [ 79 ]. Factors regulating macrophage polarization in diabetic conditions are listed in Table 2 .…”
Section: Macrophage Activation In Diabetes and Its Regulatorsmentioning
confidence: 99%